SOFTWARE FOR SEARCH AND MEASURING OF WDS CATALOG DOUBLE AND MULTIPLE STARS FROM DATABASE OF RESULTS OF CCD OBSERVATION - Protsyuk, Yu. I.; Maigurova, N. V. (Одеські астрономічні публікації, 2020)
Double and multiple star systems are the source of unique information for determining the parame- ters of star formation models and for testing stellar models evolution. Therefore observations and measuring of their mutual configuration parameters is still important. Observations of double and multiple star systems at the Research Institute “Mykolaiv Astronomical Observatory” (RI MAO) were performed with different telescopes since 2013. In addition, we also have an observational database and proceeding results of the fields in open clusters vicini- ty, which were performed using the KT-50 telescope (D=500mm, F=3000mm) in 2011–2020. All astrometric processing was carried out by the Astrometrica software using UCAC4 or GAIA DR2 as reference catalogs. The catalogs of stars positions and proper motions in the vicin- ity of open clusters that contain more than 5.6 million stars were created as results of these observations. There are a lot of double and multiple stars in the fields with open clusters, which, moreover, could be the physical member of clusters. With this aim software for search and measuring of mutual configuration parameters of the dou- ble and multiple stars from the WDS was created. Our software uses previous reduction data from Astrometrica software and allows finding stars from double and multi- ple systems, which are presented in WDS catalog. We determined separations and position angles for pairs of the found WDS systems and checked observa- tional array over 71 nights of 2019. Data of 9679 CCD images were reduced and 34277 WDS pairs were found in 7232 of them. Total numbers of unique pairs are 1504 in 1091 systems with average number of pair observations near 23. The standard errors of measurements were 0.15" for separations and 0.5° for position angles. The epoch difference between our observations and the last observa- tion in the WDS database is in the range from 2 to 28 years. The comparison with the WDS data has shown that residual differences and their standard errors are (–0.03±0.24)" in separations and (–0.07±0.88)° in position angles for close observation periods. The obtained data are of original observations that extend the observation period of stars from double and multiple systems and can be used to construct orbits and to determine the masses of compo- nents. The calculated parameters of mutual configuration of the found pairs and estimates of differences in magni- tudes of the components will be sent to the WDS database